2008
DOI: 10.2353/ajpath.2008.070829
|View full text |Cite
|
Sign up to set email alerts
|

Co-Localization of Amyloid Beta and Tau Pathology in Alzheimer's Disease Synaptosomes

Abstract: The amyloid cascade hypothesis proposes that amyloid beta (Abeta) pathology precedes and induces tau pathology, but the neuropathological connection between these two lesions has not been demonstrated. We examined the regional distribution and co-localization of Abeta and phosphorylated tau (p-tau) in synaptic terminals of Alzheimer's disease brains. To quantitatively examine large populations of individual synaptic terminals, flow cytometry was used to analyze synaptosomes prepared from cryopreserved Alzheime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
170
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 53 publications
13
170
0
Order By: Relevance
“…ajp.amjpathol.org -The American Journal of Pathology anti-Ab antibodies are sensitive to conformation and differentially label aggregated Ab preparations. 46 As previously reported, synaptic terminals from control cases show little to no Ab immunolabeling ( Figure 1C) 26,33,42,47 ; representative plots from AD cases illustrate the rise in synaptic Ab with increasing neuropathologic disease stage and the degree to which synaptic terminal Ab increases between plaque stage 0 (no plaque deposition) and stage C (end-stage plaque deposition) (Figure 1, D and E). 48 Figure 2A shows group differences in aggregate flow cytometric data [F(3,30) Z 6.13, P Z 0.002] in both early-stage (Braak II to IV) and late-stage (Braak V to VI) AD cases.…”
Section: Amyloid-b Precedes P-tau In Ad Synapsessupporting
confidence: 67%
See 4 more Smart Citations
“…ajp.amjpathol.org -The American Journal of Pathology anti-Ab antibodies are sensitive to conformation and differentially label aggregated Ab preparations. 46 As previously reported, synaptic terminals from control cases show little to no Ab immunolabeling ( Figure 1C) 26,33,42,47 ; representative plots from AD cases illustrate the rise in synaptic Ab with increasing neuropathologic disease stage and the degree to which synaptic terminal Ab increases between plaque stage 0 (no plaque deposition) and stage C (end-stage plaque deposition) (Figure 1, D and E). 48 Figure 2A shows group differences in aggregate flow cytometric data [F(3,30) Z 6.13, P Z 0.002] in both early-stage (Braak II to IV) and late-stage (Braak V to VI) AD cases.…”
Section: Amyloid-b Precedes P-tau In Ad Synapsessupporting
confidence: 67%
“…Because Western blot analysis of P-2 samples shows a strong signal for postsynaptic density protein 95, 26 it is possible that some of the Ab signal in P-2 samples arises from extracellular Ab bound to postsynaptic surface receptors, particularly heparan sulfate proteoglycan. 66 However, prior electron microscopic studies reported by our group and others document the spherical and primarily presynaptic structure of synaptosomes, 33,40 and incubation of AD synaptosomes with a combination of trypsin and heparinase does not reduce Ab labeling. Confirmation of presynaptic localization of oligomers by electron microscope would be optimal; however, detection of intraneuronal, particularly oligomeric, Ab is limited by the technical difficulty of detecting Ab antigens, which are hydrophobic and difficult to detect by conventional immunocytochemical methods, especially in postmortem tissue.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations